2010
DOI: 10.1159/000315110
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mode of Action of the Putative Sphingosine Kinase Inhibitor 2-(p-hydroxyanilino)-4-(p-chlorophenyl) Thiazole (SKI II): Induction of Lysosomal Sphingosine Kinase 1 Degradation

Abstract: Background: Sphingosine kinase 1 (SK1) is a key enzyme in the generation of sphingosine 1-phosphate (S1P) which critically regulates a variety of important cell responses such as proliferation and migration. Therefore, inhibition of SK-1 has been suggested to be an attractive approach to treat tumor growth and metastasis formation. Results: We show here that the previously developed putative SK-1 inhibitor 2-(p-hydroxyanilino)-4-(p-chlorophenyl) thiazole (SKI II) displays an additional facet of action compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…Indeed, SKI-II mediates the proteasome-dependent degradation of SK-1, leading to the inhibition of S1P generation. 43 Consistent with these data, our results indicate that pharmacologic and/or molecular inhibition of SK-1 help overcome drug resistance in CML cells via inducing PP2A-dependent dephosphorylation/inactivation and degradation of Bcr-Abl1.In this study, we also showed that S1P2 signaling contributes to drug resistance in CML via attenuation of Bcr-Abl1 dephosphorylation/degradation. Overexpression of S1P2 was not sufficient to induce drug resistance, and it required the addition of S1P in K562 cells, suggesting that SK-1-generated S1P is necessary for the inhibition of PP2A and regulation of imatinib resistance upstream of S1P2 signaling.…”
supporting
confidence: 89%
“…Indeed, SKI-II mediates the proteasome-dependent degradation of SK-1, leading to the inhibition of S1P generation. 43 Consistent with these data, our results indicate that pharmacologic and/or molecular inhibition of SK-1 help overcome drug resistance in CML cells via inducing PP2A-dependent dephosphorylation/inactivation and degradation of Bcr-Abl1.In this study, we also showed that S1P2 signaling contributes to drug resistance in CML via attenuation of Bcr-Abl1 dephosphorylation/degradation. Overexpression of S1P2 was not sufficient to induce drug resistance, and it required the addition of S1P in K562 cells, suggesting that SK-1-generated S1P is necessary for the inhibition of PP2A and regulation of imatinib resistance upstream of S1P2 signaling.…”
supporting
confidence: 89%
“…The biologic significance of different SphK1 forms is not known, although it has been suggested that they exhibit different subcellular localization (40) and may therefore have functional specificity. The SphK1 variants were all decreased by SKi-II and, as in other cell types (27,41,42), this was reversed by the proteasome inhibitor MG132, implying their degradation via ubiquitin-proteasomal pathways. MG132 also increased various SphK1 forms to levels above those in untreated cells, suggesting proteasome regulation of the enzyme under basal conditions.…”
Section: Discussionmentioning
confidence: 72%
“…S2). In addition to this, others have reported, using the cathepsin B inhibitor, CA074Me, that SKi induces lysosomal degradation of SK1 in human podocytes (32). To investigate the role for lysosomal degradation of SK1a/b in response to SKi, we pretreated LNCaP cells with CA074Me.…”
Section: Effect Of Sk1 Inhibitors In Human Pulmonary Artery Smooth Mumentioning
confidence: 94%